Sway-Based Interactive Chemistry Learning Media: Feasibility for Improving Students’ Conceptual Understanding and Self-efficacy - Siti Nor Laily Hikmah; Parham Saadi; Arif Sholahuddin (Jurnal Penelitian Pendidikan IPA, 2023)
Self-efficacy greatly determines the success of students in learning. However, most students have low self-efficacy. This study aims to develop sway-based interactive chemistry learning media to improve the students’ conceptual understanding of stoichiometry and self-efficacy. The research used a 4D development model which consists of the stages of define, design, develope, and disseminate. Sway-based media trials include individual trials involving 3 students, small group trials involving 8 students, and field trials involving 2 classes consisting of 70 students of class X MIPA SMA Negeri 4 Banjarmasin. The study indicated that the developed sway-based media: (1) very valid from the aspect of content, presentation, language, and media; (2) practical based on one to one and small group trials, students’ responses, and learning process management data; and (3) effective based on the N-gain score of the students’ conceptual understanding of stoichiometric concept and self-efficacy in the medium and high categories, respectively. It can be concluded that sway-based interactive learning media is feasible used in chemistry learning to improve students’ conceptual understanding of stoichiometric concepts and self-efficacy.